Ripple Effect Analysis on Coffee Supply Chain During Covid-19 Pandemic - Muflihat, Syakia (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study examines the disruption of the coffee supply chain due to the Covid-19 outbreak in the world. During the Covid-19 pandemic, demand and delivery disruptions occurred at PT Toduri Kopi. This study aims to identify the disruption risks in the supply chain during the pandemic and analyze the impact of ripple effects on supply chain performance in PT Toduri Kopi. Discrete event simulation (DES) is used to simulate ripple effect problems in the supply chain. AnyLogistix was chosen to help analyze the disruption before and during a pandemic and its impact on supply chain performance. The results of this simulation show that there is a decrease in demand by 25%, a decrease in profit by 49.5%, a decrease in revenue by 40.9% and a total cost of 7.59%.